Employability of Special Education Graduates according to Indonesian National Accreditation Standard - Ardianingsih, Febrita; Wijiastuti, Asri; Widajati, Wiwik; Mahmudah, Siti (Department of Special Education, 2022)
Accreditation of the Undergraduate Program of Special Education (UPSE) in Indonesia is still carried out by the National Accreditation Agency for Higher Education (BAN-PT) based on national higher education standards. One of the assessment elements is graduates employability. The aim of this research is to describe the employability of special education graduates according to BAN-PT standard. This research is a survey with a cross sectional design. Respondents were 161 graduates of the UPSE Universitas Negeri Surabaya (UNESA) spread across Bangka Belitung, Banten, DKI Jakarta, Yogyakarta, West Java, Central Java, East Java, South Kalimantan, West Nusa Tenggara, and Papua. Data were collected using online questionnaire and analyzed quantitatively. The results are: (1) the average waiting period of the graduates is 3.8 months, and (2) 88% of graduate employments have compatibility with the field of study. Therefore, it can be concluded that the employability of special education graduates has met the highest standards according to the BAN-PT. Research findings also indicate that the UPSE is able to produce quality graduates who have skills that support employability so that graduates are quickly absorbed in the world of work that match with their field of study.